Estimating particle size and velocity from fluorescence pulses: A practical validation study of flow cytometry signals analysis - Megan A. Catterton; Matthew DiSalvo; Paul N. Patrone; Gregory A. Cooksey (PLoS ONE, 2026)
When particles cross optimal measurement regions in a flow cytometer, they generate time-resolved signals (pulses) that contain valuable information. However, this information is lost when signals are reduced to scalars such as area, width, and height. Because flow cytometers convolve particle properties with the laser profile and geometric factors of the optical interrogation region, it is in theory possible to estimate the particle diameter, velocity, and brightness (effectively its fluorophore concentration or scattering factors) from the time-resolved data alone. Here, we independently vary the velocity, size and dye concentration to validate their unique contributions to signal shape under flow conditions in which particle trajectories are well controlled. Through a series of flow rate variations on microspheres of known size and fluorophore concentrations, we study the magnitude of changes in time-resolved signals and the impact on estimation of particle properties. The method was applied to cells labeled with a DNA binding dye, which is frequently used to classify cells whether cells are in pre- (G0/G1; 1x DNA label) or post mitosis (G2; 2x DNA label) phase of the cell cycle. Using our signals analysis, we found a 1.26-fold increase in the apparent diameter from G0/G1 to G2 populations. This shift corresponds to an approximate doubling of the volume of a sphere, which is consistent with literature and microscopy data. Overall, this work validates that fluorescence pulses acquired in flow cytometry can be used to estimate and remove sources of uncertainty (e.g., due to velocity changes) and to extract information about the size, velocity, and biomarker concentrations of particles and cells.